The People's Representative Council's Right to Inquiry: Opportunities and Challenges in Upholding Democracy in Indonesia - Anwar Hidayat (Jurnal Restorasi : Hukum dan Politik, 2024)
The 2024 General Election which has just finished has left a number of dissatisfied with the results of the general election, including the election of president and vice president. A number of political parties have begun to discuss the use of the right to inquiry in the DPR RI. The idea of the right to inquiry in this election itself is considered a form of upholding democracy in Indonesia. Therefore, this research aims to analyze the People's Representative Council (DPR) right to inquiry as a vital instrument in the context of upholding democracy in Indonesia. Within a theoretical framework that combines the principles of representative democracy and political accountability, this research explores the opportunities and challenges faced by DPR inquiry rights in practice. This research uses a normative legal approach through the applicable legislation approach. The research results show that the implementation of the DPR's right to inquiry in upholding democracy in Indonesia involves a series of complex stages. Even though there are challenges such as strict requirements and a long process, if successfully passed, the inquiry committee will have broad authority to investigate alleged violations by the government. This reflects the DPR's serious efforts to carry out its oversight function over the government and ensure government accountability towards the people. Thus, the implementation of the right to inquiry is expected to strengthen the integrity and balance of power in the Indonesian democratic system.